Species distribution of the Halophilous-psamophilous community along the coast of the Espirito-Santo state - Thomaz, L. D.; Monteiro, R. (Inst Tecnologia Parana, 1993)
The purpose of the present work was the study of the composition and distribution of the species in halophilous-psamophilous communities, utilizing the square method in 10 beaches of the Espirito Santo coast. The data of presence and cover of each species for the calculation of frequency and dominance, respectively, were obtained from twenty contiguous square of each of five 20 meters samplings, in a total of one hundred squares for each beach. Mariscus pedunculatus, Panicum racemosum, Ipomoea pes-caprae, I. littoralis and Blutaparon portulacoides were the most dominant species in the analyzed beaches.
Keywords: HALOPHILOUS-PSAMOPHILOUS COMMUNITY; SPECIES DISTRIBUTION; BEACH